2017
DOI: 10.18860/jia.v4i4.4499
|View full text |Cite
|
Sign up to set email alerts
|

Universal Design and Accessibility for People With Disabilities in Masjid Negara, Malaysia

Abstract: Malaysia to become seeks to become a fully developed country by 2020. Among nine central challenges demonstrated in the body of the "Vision 2020" is "the challenge of establishing a fully caring society" (WAWASAN 2020). Along with developed societies overcoming such dysfunctional built environments has become under consideration in Malaysia as well to remove barriers and provide equal access of people with disabilities (PWDS) to all public services. Notwithstanding practical steps taken, there are still dissa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…However, a considerable amount of literature has been published on universal design in public masjid. Studies by Asiah Abdul Rahim 2014and Utaberta, et al (2017) revealed the same result as most of the person with the disability in Malaysia express their frustration in masjid design. Furthermore, having a universal design is important because the masjid is the most visited place at any time by people (Asiah Abdul Rahim, 2014).…”
Section: Universal Design In Public Buildingmentioning
confidence: 76%
See 1 more Smart Citation
“…However, a considerable amount of literature has been published on universal design in public masjid. Studies by Asiah Abdul Rahim 2014and Utaberta, et al (2017) revealed the same result as most of the person with the disability in Malaysia express their frustration in masjid design. Furthermore, having a universal design is important because the masjid is the most visited place at any time by people (Asiah Abdul Rahim, 2014).…”
Section: Universal Design In Public Buildingmentioning
confidence: 76%
“…Even so previous studies mostly reported on the general public buildings, there is still a lack of studies on awarded buildings such as Green Building Index (GBI). Therefore, this study evaluated the GBI building by limitation to the masjid as Muslims are the majority in Malaysia according to Utaberta, et al (2018).…”
Section: Universal Design In Public Buildingmentioning
confidence: 99%
“…For the Muslim community, mosque is a necessity in fulfilling the preservation of five essentials of maqasid al-shari'ah of faith, self, intellect, lineage, and property, in its respective ways (Asiah, Azila, et al, 2015). According to JAKIM, Malaysian mosques classifies into five general groups, and mosques usually are the principal, state, and some private funded mosques (Asiah, Azila, et al, 2015;MS2577:2014MS2577: , 2014Utaberta, Niya et al, 2017).…”
Section: Mosque Design; Modern and Heritage Mosquementioning
confidence: 99%
“…As elaborated by Asiah, Azila, et al (2015), mosque institution is also devised towards providing supports for the PwDs through its activities and number of programs are among the elements assessed in increasing mosques' ratings. The importance of providing accessibility is to give the PwDs an equal opportunity for them to perform congregational prayers in respect of helping them perform their obligation as other devoted Muslims (Asiah & Nur Amirah, 2014;Utaberta et al, 2017).…”
Section: Community Inclusion and Mosque Accessibilitymentioning
confidence: 99%
See 1 more Smart Citation